Latent simian varicella virus reactivates in monkeys treated with tacrolimus with or without exposure to irradiation - Mahalingam, Ravi (2010)
Simian varicella virus (SVV) infection of primates resembles human varicellazoster virus (VZV) infection. After primary infection, SVV becomes latent in ganglia and reactivates after immunosuppression or social and environmental stress. Herein, natural SVV infection was established in 5 cynomolgus macaques (cynos) and 10 African green (AG) monkeys. Four cynos were treated with the immunosuppressant tacrolimus (80 to 300 μg/kg/day) for 4 months and 1 was untreated (group 1). Four AG monkeys were exposed to a single dose (200 cGy) of x-irradiation (group 2), and 4 other AG monkeys were irradiated and treated with tacrolimus for 4 months (group 3); the remaining 2 AG monkeys were untreated. Zoster rash developed 1 to 2 weeks after tacrolimus treatment in 3 of 4 monkeys in group 1, 6 weeks after irradiation in 1 of 4 monkeys in group 2, and 1 to 2 weeks after irradiation in all 4 monkeys in group 3. All monkeys were euthanized 1 to 4 months after immunosuppression. SVV antigens were detected immunohistochemically in skin biopsies as well as in lungs of most monkeys. Low copy number SVV DNA was detected in ganglia from all three groups of monkeys, including controls. RNA specific for SVV ORFs 61, 63, and 9 was detected in ganglia from one immunosuppressed monkey in group 1. SVV antigens were detected in multiple ganglia from all immunosuppressed monkeys in every group, but not in controls. These results indicate that tacrolimus treatment produced reactivation in more monkeys than irradiation and tacrolimus and irradiation increased the frequency of SVV reactivation as compared to either treatment alone.